The Fate of Type II Odontoid Fractures after Posterior Atlantoaxial Fusion: Where Does Healing Occur? - Bisson, Erica F.; Mumert, Michael L.; Mazur, Marcus D.; Dailey, Andrew T.; Schmidt, Meic H. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2015)
Background Anderson and D'Alonzo type II odontoid fractures often require surgical intervention. Our goal was to understand the pattern of healing in patients who had a posterior atlantoaxial fusion for a type II odontoid fracture.Methods We conducted a retrospective study of patients who underwent posterior atlantoaxial instrumentation and fusion for a type II odontoid fracture at our institution between 1987 and 2011. Patients who had fusion evaluation by computed tomography (CT) scan ≥3 months after surgery were included. Surgical technique included placement of a posterior bone graft with transarticular screws, C1 lateral mass and C2 pars/pedicle screw construct, or a combination of screw fixation techniques. Postoperative CT scans were reviewed to determine the site where fusion occurred.Results Sixty-four patients underwent posterior atlantoaxial instrumentation and fusion for type II odontoid fractures, 12 of whom had fusion evaluation by CT scan. A total of 11 of 12 patients had fusion across the fracture site, 2 across the C1–C2 joint, and 11 at the posterior graft site. All 12 patients had at least one site of fusion.Conclusions There is a high rate of fusion across the fracture site of a type II odontoid fracture after posterior atlantoaxial fixation. In young patients with acute type II fractures who are not candidates for anterior screw fixation, posterior atlantoaxial instrumentation without fusion may be sufficient for fracture healing, thus allowing for the possibility of implant removal and preservation of C1–C2 motion.
Keywords: type II odontoid fracture; C1–C2; posterior atlantoaxial fusion; bone graft